QUANTIFICATION AND HEALTH RISK ASSESSMENT OF HEAVY METALS IN FRESH AND GRILLED SAUSAGES SOLD IN THE TAMALE METROPOLIS, GHANA - Logochura, S.; Cobbina, S. J.; Ofori, S. A. (UDS International Journal of Development, 2020)
Heavy metals concentrations are in greater levels in major cities or industrial areas than they would exist in the natural environment. They pose a serious threat to humans due to their characteristic toxicity, bioaccumulation and bio-magnifications in the food chain. Street foods like meat products such as grilled sausages pose a potential health risk to regular consumers as a result of their exposure to the open surroundings. This study reports on the presence and levels as well as the potential associated health risks of Lead (Pb), Manganese (Mn), Iron (Fe) and Copper (Cu) in fresh and grilled sausages sold in the Tamale metropolis. The samples were analyzed using the Atomic Absorption Spectrophotometer (AAS). Lead was not detected in either of the samples. The average levels of Copper, Manganese and Iron were 0.3057 ± 0.0918 mg/kg, 0.1657 ± 0.0054 mg/kg and 1.2436 ± 0.1664 mg/kg, respectively for the fresh samples. The average levels of Copper, Manganese and Iron recorded in the grilled samples were 0.0470 ± 0.0096 mg/kg, 0.1512 ± 0.0048 mg/kg and 1.3242 ± 0.1881 mg/kg, respectively. The health risks assessment conducted indicated that there were no possible risks of cancer posed towards the consumers. Keywords: Heavy metals, Sausages, bioaccumulate, risk assessment, carcinogenic risk, grill, contamination